2015
DOI: 10.1093/glycob/cwv041
|View full text |Cite
|
Sign up to set email alerts
|

Structural glycobiology of human α1-acid glycoprotein and its implications for pharmacokinetics and inflammation

Abstract: Human α1-acid glycoprotein (AGP) is an abundant human plasma glycoprotein that may be N-glycosylated at five positions. AGP plays important roles on pharmacokinetics and can rise up to 5-fold in inflammatory events. In such events, the glycan chains attached to Asn54, Asn75 and Asn85 may become fucosylated, originating a sialyl-Lewis X epitope. This epitope, in turn, can bind selectin proteins. Such interplay is important for immunomodulation. While the X-ray structure of unglycosylated AGP has been reported, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 44 publications
2
31
0
2
Order By: Relevance
“…AGP is an acute-phase reactant described as an immunomodulator and a major binding protein for endogenous ligands and drugs ( 51 ). AGP has 5 predicted N-glycosylation sites, with over 150 glycoforms that affect the AGP-ligand-binding site and change protein dynamics ( 52 , 53 ). We speculate that further study of the differential biological function of AGP glycoforms, driven in part by ZIP8 391-Thr genotype and abnormal Mn homeostasis, may reveal mechanistic underpinnings of the pleiotropic disease associations of ZIP8 391-Thr.…”
Section: Discussionmentioning
confidence: 99%
“…AGP is an acute-phase reactant described as an immunomodulator and a major binding protein for endogenous ligands and drugs ( 51 ). AGP has 5 predicted N-glycosylation sites, with over 150 glycoforms that affect the AGP-ligand-binding site and change protein dynamics ( 52 , 53 ). We speculate that further study of the differential biological function of AGP glycoforms, driven in part by ZIP8 391-Thr genotype and abnormal Mn homeostasis, may reveal mechanistic underpinnings of the pleiotropic disease associations of ZIP8 391-Thr.…”
Section: Discussionmentioning
confidence: 99%
“…From the X-ray crystal structure of recombinant AGP, in which all glycans were removed, it is evident that the N-glycans at Asn-38 and -75 are close to the drug-binding cavity and variable N-glycosylation, especially fucosylation, may modulate access of the cavity to warfarin ( 17 ). A previous molecular-dynamics study of AGP revealed that glycosylation expands the volume of the hydrophobic cavity for drug binding ( 47 ). Although other glycosylation sites are far from the hydrophobic cavity, the occurrence of distal antennary fucosylation and N-glycan branching/elongation may induce conformational changes to the AGP protein backbone, contributing to a weaker protein–drug interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Alpha 1 -acid glycoprotein (AGP) is an acute phase glycoprotein and serum transport protein with a low isoelectric point (pI, 2.8–3.8) and a high carbohydrate content (40%) [1,2]. The normal concentration of this protein in human plasma is 0.5–1.0 g/L (or 12–24 μM); however, this concentration can increase by up to ten-fold in some diseases [1].…”
Section: Introductionmentioning
confidence: 99%